Preparation method and application of carbon-coated fluorine-doped sodium ferric sulfate positive electrode material

By doping F elements into the Na2Fe2(SO4)3 positive electrode material and performing carbon coating, the problems of the polarization phenomenon, low specific capacity and poor cycle stability of the material are solved, and higher electrochemical performance and stability are achieved.

CN119430295APending Publication Date: 2025-02-14ZHEJIANG SCI-TECH UNIV

Patent Information

Application Number
CN202411681784.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Na2Fe2(SO4)3 positive electrode material has obvious polarization phenomena, low specific capacity, poor circulation stability, poor thermal stability, and water sensitivity in sodium ion batteries.

Method used

By doping F elements, the distribution of O2- in Na2Fe2(SO4)3 is changed, and spray drying combined with calcination treatment is used to prepare carbon-coated fluorine-doped Na2Fe2(SO4)3 positive electrode material to improve its electron conductivity and sodium ion diffusion dynamics.

Benefits of technology

The cyclic stability, electrochemical sodium storage performance and air stability of the cathode material are significantly improved, the resistance is reduced, and electron conduction is accelerated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430295A_ABST
    Figure CN119430295A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of positive electrode materials, and discloses a preparation method of a carbon-coated fluorine-doped sodium ferric sulfate positive electrode material, which comprises the following steps: step 1, adding an iron source, a sodium source, a sulfur source, a carbon source and a fluorine source into deionized water, and heating and stirring to completely dissolve the raw materials to obtain a solution A; 2, converting the solution A into precursor powder B by using a spray drying method; and 3, calcining the precursor powder B in an inert atmosphere, and crushing and grinding the obtained product to obtain the carbon-coated fluorine-doped Na2Fe2 (SO4) 3 positive electrode material. The F element with higher electronegativity than the S element is introduced, so that the overall electron distribution of the material is changed, the structural stability is improved, and the high-conductivity carbon protection layer is coated on the surface of the active material to form a conductive network, so that the resistance is reduced, the volume expansion is relieved, and the battery capacity and the cycling stability can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of positive electrode materials, and more specifically relates to a preparation method and application of a carbon-coated fluorine-doped sodium iron sulfate positive electrode material. Background Art

[0002] With the intensification of the global energy crisis and the increasing severity of environmental pollution, the development of clean and renewable energy has become an urgent need for global energy transformation. Electrochemical energy storage technology, especially lithium-ion batteries, has played an important role in integrating and optimizing the use of clean energy in the power grid due to its flexibility and reliability. However, with the rapid development of the new energy vehicle industry and large-scale electrochemical energy storage systems, the global demand for lithium resources continues to increase, and supply shortage pressure has begun to emerge. At the same time, the scarcity and price fluctuations of lithium resources limit its application in large-scale energy storage.

[0003] Sodium-ion batteries have become a potential alternative technology in the field of electrochemical energy storage due to their abundant raw material resources and low cost. The choice of positive electrode materials for sodium-ion batteries directly affects the performance and manufacturing cost of the battery. At present, research on positive electrode materials mainly includes three types of materials: transition metal layered oxides, Prussian blue analogs, and polyanion compounds. Among them, polyanion compounds have received more attention due to their excellent rate performance, cycle life and safety. Na2Fe2(SO4)3, as a typical representative of iron-based polyanion positive electrode materials, has a higher operating voltage and lower raw material cost than phosphate polyanion compounds, giving it dual advantages in performance and economy. However, Na2Fe2(SO4)3 still faces many challenges as a positive electrode material for sodium-ion batteries: (1) poor thermal stability, temperature fluctuations can cause structural changes; (2) a large band gap hinders the rapid transfer of carriers and limits the battery's charging and discharging efficiency; (3) low intrinsic conductivity leads to an increase in the battery's internal resistance, which reduces the overall energy efficiency and power output; (4) it is sensitive to moisture, and even trace amounts of water in contact with it can destroy its structure and form a hydrated phase.

[0004] In response to the above problems, researchers have improved its conductivity and stability through various means such as surface modification, optimization of material structure, trace ion doping and size nano-sizing. For example, patent CN115312781A discloses a method for preparing Na2Fe2(SO4)3 core-shell structure by solution evaporation method, and its structure is Na2Fe2(SO4)3 core, titanium oxide coating layer and carbon material coating layer from inside to outside, which improves the defective activity of Na2Fe2(SO4)3 and improves the electron transfer efficiency. However, the core-shell structure cannot be completed in one step during the synthesis process, and the steps are cumbersome, which brings difficulties to the application of large-scale production. For example, patent CN118164458A discloses the preparation of phosphate anion-doped Na2Fe2(SO4)3 as a positive electrode material for sodium ion batteries by ball milling. The multi-anion framework expands the structural gap and can accommodate more sodium ions for reversible deintercalation and insertion therein. However, the ball milling process takes a long time to prepare, and material agglomeration is inevitable. Therefore, developing efficient, low-cost and highly safe Na2Fe2(SO4)3 preparation technology is crucial to promoting its large-scale application in energy storage batteries. Summary of the invention

[0005] The main purpose of the present invention is to provide a method for preparing a carbon-coated fluorine-doped sodium iron sulfate positive electrode material and its application, by introducing F elements with stronger electronegativity than S elements, so as to promote the partial O in Na2Fe2(SO4)3 2- From SO4 2- The delocalized migration in the electrolyte changes the overall electron distribution of the material, thus solving a series of problems of the existing Na2Fe2(SO4)3 cathode materials, such as obvious polarization, low specific capacity, and poor cycle stability. The Na2Fe2(SO4)3 cathode material was prepared by spray drying combined with calcination treatment, and carbon coating and fluorine doping were performed at the same time to improve the electronic conductivity, sodium ion diffusion kinetics, and electrochemical sodium storage performance of the cathode material.

[0006] At the same time, the present invention adopts two carbon sources to carry out carbon coating in coordination, and carbon nanotubes are used as the main carbon source coating substrate. Citric acid and ascorbic acid can cross-link the active substances while assisting carbon nanotubes to achieve better carbon coating effect on the surface of fluorine-doped sodium ferric sulfate. Both citric acid and ascorbic acid have a reducing effect, which can protect divalent iron from being oxidized to trivalent iron in the solution. Compared with citric acid, ascorbic acid has a stronger reducing property, which can effectively remove free radicals and inhibit oxidation of the electrode surface, and can also form a protective film on the contact surface of the electrode electrolyte, effectively inhibiting side reactions and electrolyte decomposition, and further improving the stability of the sodium ferric sulfate positive electrode material.

[0007] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0008] One of the technical solutions of the present invention: a method for preparing a carbon-coated fluorine-doped sodium iron sulfate positive electrode material, comprising the following steps:

[0009] Step 1: adding an iron source, a sodium source, a sulfur source, a carbon source and a fluorine source into deionized water, and heating and stirring to completely dissolve the raw materials to obtain a solution A; the carbon source is a mixture of a carbon source I and a carbon source II, the carbon source I is a carbon nanotube, and the carbon source II is one or both of citric acid and ascorbic acid;

[0010] Step 2: Convert solution A into precursor powder B using a spray drying method;

[0011] Step 3: Calcine the precursor powder B under inert atmosphere conditions, crush and grind the obtained product to obtain a carbon-coated fluorine-doped Na2Fe2(SO4)3 positive electrode material.

[0012] Preferably, in step 1, the iron source is any one or more of ferrous sulfate heptahydrate, ammonium ferrous sulfate, anhydrous ferrous sulfate and ferrous acetate.

[0013] Preferably, in step 1, the sodium source is any one or more of sodium oxalate, sodium bicarbonate, anhydrous sodium acetate, sodium citrate, sodium sulfide, sodium salicylate and sodium hydroxide.

[0014] Preferably, in step 1, the sulfur source is any one or more of anhydrous sodium sulfate, potassium sulfate and ammonium sulfate. Preferably, in step 1, the fluorine source is any one or more of sodium fluoride, potassium fluoride and sodium trifluoroacetate. Preferably, in step 1, the molar ratio of the iron source, sodium source, sulfur source, carbon source and fluorine source is (1.0-2.5): (1.0-2.5): (1.0-2.5): (0.1-1.0): (0.01-1).

[0015] Preferably, in step 1, the molar ratio of carbon source I to carbon source II is 2:1-1.5.

[0016] Preferably, in step 1, the heating and stirring method is to add the raw materials in order according to the ratio into deionized water, stir for 10 to 90 minutes, and then ultrasonically disperse for 10 to 90 minutes to obtain solution A.

[0017] Preferably, in step 2, the inlet temperature of the spray drying is 100-230° C., the outlet temperature is 100-120° C., and the feed rate is 5-25%.

[0018] The feed rate is the ratio of the actual feed rate to the maximum feed rate that the equipment can accept.

[0019] Preferably, in step 3, the inert gas protective atmosphere for calcination is one of argon, argon-hydrogen mixture and nitrogen; the calcination conditions are: first increase the temperature to 100-200°C at a heating rate of 1-4°C / min, keep warm for 1-6h, then increase the temperature to 200-500°C at a heating rate of 1-5°C / min, and keep warm for 10-25h.

[0020] The second technical solution of the present invention: Application of the carbon-coated fluorine-doped sodium iron sulfate positive electrode material prepared by the above preparation method in a sodium ion battery.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] (1) Taking advantage of the hydrophobicity of carbon nanotubes, they were coated on the surface of the active material Na2Fe2(SO4)3. Under the premise of avoiding the influence of the hydrated impurity phase Na2Fe2(SO4)3·4H2O, the carbon-coated fluorine-doped Na2Fe2(SO4)3 was prepared by a simple spray drying method combined with calcination treatment in a liquid medium. This preparation method is fast, efficient, and easy to scale up. The product particles are uniform, and the size and shape are stable and controllable.

[0023] (2) The introduction of F elements with stronger electronegativity than S elements induces local polarization or changes in electron density in the surrounding bonding environment, affecting the O 2- In SO4 2- The stability of the group promotes the partial O 2- From SO4 2- The delocalized migration in the material changes the overall electron distribution of the material, thus solving a series of problems of the existing Na2Fe2(SO4)3 positive electrode materials, such as obvious polarization, low specific capacity, and poor cycle stability. In addition, the lattice is expanded, which reduces the stress accumulation during the electrochemical cycle and improves the structural stability. The highly conductive carbon protective layer is coated on the surface of the active material to form a conductive network, which reduces the resistance and accelerates the electron conduction. At the same time, the carbon protective layer isolates the Na2Fe2(SO4)3 particles from the environment, F - The incorporation of reduces the adsorption capacity of active sites on the surface of the material for polar molecules (water). The combined effect of the two greatly improves the air stability of Na2Fe2(SO4)3. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The carbon-coated fluorine-doped Na 2.05 Fe2(SO4)3F 0.05 Positive electrode material and comparative example 1 Carbon-coated Na2Fe2(SO4)3 positive electrode material as rate performance diagram of positive electrode material for sodium ion battery;

[0025] Figure 2 The carbon-coated fluorine-doped Na 2.05 Fe2(SO4)3F 0.05 SEM image of positive electrode material;

[0026] Figure 3 This is the SEM image of the carbon-coated Na2Fe2(SO4)3 positive electrode material prepared in Comparative Example 1;

[0027] Figure 4 The carbon-coated fluorine-doped Na 2.05 Fe2(SO4)3F 0.05 X-ray diffraction pattern of cathode material;

[0028] Figure 5 The carbon-coated fluorine-doped Na 2.05 Fe2(SO4)3F 0.05 The first charge and discharge curve of the positive electrode material at 0.2C;

[0029] Figure 6 The carbon-coated fluorine-doped Na 2.05 Fe2(SO4)3F 0.05 Positive electrode material and comparative example 1 Carbon-coated Na2Fe2(SO4)3 positive electrode material as a cycling performance diagram of the positive electrode material for sodium ion batteries. DETAILED DESCRIPTION

[0030] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.

[0031] Example 1

[0032] Carbon-coated fluorine-doped Na 2.01 Fe2(SO4)3F 0.01 Preparation of positive electrode materials:

[0033] Step 1: Anhydrous ferrous sulfate, anhydrous sodium sulfate, sodium fluoride, carbon nanotubes and ascorbic acid are added to 50 mL of deionized water in a molar ratio of 2:1:0.01:0.02:0.01 (wherein the molar amount of anhydrous ferrous sulfate is 2 mol). The raw materials are completely dissolved by heating and stirring to obtain a uniform light green clear solution A.

[0034] Step 2: Use a spray drying method to spray the uniform solution A into precursor powder B, with the specific parameters being: 100% air inlet rate, 200°C air inlet temperature, and 15% feed rate (the maximum feed rate acceptable to the equipment is 100% of the maximum pump speed).

[0035] Step 3: Transfer the precursor powder B to a tube furnace for calcination. The calcination conditions are: in an argon atmosphere, first increase the temperature to 150°C at a rate of 3°C / min, keep the temperature for 4 hours, then increase the temperature to 400°C at a rate of 5°C / min, and keep the temperature for 20 hours. The calcined product is crushed, ground and sieved to obtain carbon-coated fluorine-doped Na 2.01 Fe2(SO4)3F 0.01 Positive electrode material.

[0036] Example 2

[0037] Carbon-coated fluorine-doped Na 2.05 Fe2(SO4)3F 0.05 Preparation of positive electrode materials:

[0038] Step 1: Anhydrous ferrous sulfate, anhydrous sodium sulfate, sodium fluoride, carbon nanotubes and ascorbic acid are added to 50 mL of deionized water in a molar ratio of 2:1:0.05:0.02:0.01 (wherein the molar amount of anhydrous ferrous sulfate is 2 mol). The raw materials are completely dissolved by heating and stirring to obtain a uniform light green clear solution A.

[0039] Step 2: Use a spray drying method to spray the uniform solution A into precursor powder B, with the specific parameters being: 100% air inlet rate, 200°C air inlet temperature, and 15% feed rate (the actual feed rate accounts for the maximum feed rate of 100% acceptable to the equipment).

[0040] Step 3: Transfer the precursor powder B to a tube furnace for calcination. The calcination conditions are: in an argon atmosphere, first increase the temperature to 150°C at a rate of 3°C / min, keep the temperature for 4 hours, then increase the temperature to 400°C at a rate of 5°C / min, and keep the temperature for 20 hours. The calcined product is crushed, ground and sieved to obtain carbon-coated fluorine-doped Na 2.05 Fe2(SO4)3F 0.05 Positive electrode material.

[0041] Example 3

[0042] Carbon-coated fluorine-doped Na 2.1 Fe2(SO4)3F 0.1 Preparation of positive electrode materials:

[0043] Step 1: Anhydrous ferrous sulfate, anhydrous sodium sulfate, sodium fluoride, carbon nanotubes and ascorbic acid are added to 50 mL of deionized water in a molar ratio of 2:1:0.1:0.02:0.01 (wherein the molar amount of anhydrous ferrous sulfate is 2 mol). The raw materials are completely dissolved by heating and stirring to obtain a uniform light green clear solution A.

[0044] Step 2: Use a spray drying method to spray the uniform solution A into precursor powder B, with the specific parameters being: 100% air inlet rate, 200°C air inlet temperature, and 15% feed rate (the maximum feed rate acceptable to the equipment is 100% of the maximum pump speed).

[0045] Step 3: Transfer the precursor powder B to a tube furnace for calcination. The calcination conditions are: in an argon atmosphere, first increase the temperature to 150°C at a rate of 3°C / min, keep the temperature for 4 hours, then increase the temperature to 400°C at a rate of 5°C / min, and keep the temperature for 20 hours. The calcined product is crushed, ground and sieved to obtain carbon-coated fluorine-doped Na 2.1 Fe2(SO4)3F 0.1 Positive electrode material.

[0046] Example 4 (Changing the amount of carbon nanotubes and ascorbic acid added in Example 1)

[0047] Carbon-coated fluorine-doped Na 2.01 Fe2(SO4)3F 0.01 Preparation of positive electrode materials:

[0048] Step 1: Anhydrous ferrous sulfate, anhydrous sodium sulfate, sodium fluoride, carbon nanotubes and ascorbic acid are added to 50 mL of deionized water in a molar ratio of 2:1:0.01:0.03:0.02 (wherein the molar amount of anhydrous ferrous sulfate is 2 mol). The raw materials are completely dissolved by heating and stirring to obtain a uniform light green clear solution A.

[0049] Step 2: Use a spray drying method to spray the uniform solution A into precursor powder B, with the specific parameters being: 100% air inlet rate, 200°C air inlet temperature, and 15% feed rate (the maximum feed rate acceptable to the equipment is 100% of the maximum pump speed).

[0050] Step 3: Transfer the precursor powder B to a tube furnace for calcination. The calcination conditions are: in an argon atmosphere, first increase the temperature to 150°C at a rate of 3°C / min, keep the temperature for 4 hours, then increase the temperature to 400°C at a rate of 5°C / min, and keep the temperature for 20 hours. The calcined product is crushed, ground and sieved to obtain carbon-coated fluorine-doped Na 2.01 Fe2(SO4)3F 0.01 Positive electrode material.

[0051] Example 5 (replacing the ascorbic acid in Example 1 with citric acid)

[0052] Carbon-coated fluorine-doped Na 2.01 Fe2(SO4)3F 0.01 Preparation of positive electrode materials:

[0053] Step 1: Add anhydrous ferrous sulfate, anhydrous sodium sulfate, sodium fluoride, carbon nanotubes and citric acid in a molar ratio of 2:1:0.01:0.02:0.01 (wherein the molar amount of anhydrous ferrous sulfate is 2 mol) into 50 mL of deionized water in sequence. Heat and stir to completely dissolve the raw materials to obtain a uniform light green clear solution A.

[0054] Step 2: Use a spray drying method to spray the uniform solution A into precursor powder B, with the specific parameters being: 100% air inlet rate, 200°C air inlet temperature, and 15% feed rate (the maximum feed rate acceptable to the equipment is 100% of the maximum pump speed).

[0055] Step 3: Transfer the precursor powder B to a tube furnace for calcination. The calcination conditions are: in an argon atmosphere, first increase the temperature to 150°C at a rate of 3°C / min, keep the temperature for 4 hours, then increase the temperature to 400°C at a rate of 5°C / min, and keep the temperature for 20 hours. The calcined product is crushed, ground and sieved to obtain carbon-coated fluorine-doped Na 2.01 Fe2(SO4)3F 0.01 Positive electrode material.

[0056] Comparative Example 1 (without fluorine doping)

[0057] Preparation of carbon-coated Na2Fe2(SO4)3 cathode material:

[0058] Step 1: Add anhydrous ferrous sulfate, anhydrous sodium sulfate, carbon nanotubes and ascorbic acid in a molar ratio of 2:1:0.02:0.01 (wherein the molar amount of anhydrous ferrous sulfate is 2 mol) into 50 mL of deionized water in sequence. Heat and stir to completely dissolve the raw materials to obtain a uniform light green clear solution A.

[0059] Step 2: Use a spray drying method to spray the uniform solution A into precursor powder B, with the specific parameters being: 100% air inlet rate, 200°C air inlet temperature, and 15% feed rate (the actual feed rate accounts for the maximum feed rate of 100% acceptable to the equipment).

[0060] Step 3: Transfer the precursor powder B to a tube furnace for calcination. The calcination conditions are: in an argon atmosphere, first increase the temperature to 150°C at a heating rate of 3°C / min, keep it warm for 4 hours, then increase the temperature to 400°C at a heating rate of 5°C / min, and keep it warm for 20 hours. The calcined product is crushed, ground and sieved to obtain a carbon-coated Na2Fe2(SO4)3 positive electrode material.

[0061] Comparative Example 2 (without fluorine doping and carbon coating)

[0062] Preparation of Na2Fe2(SO4)3 positive electrode material:

[0063] Step 1: Add anhydrous ferrous sulfate and anhydrous sodium sulfate in a molar ratio of 2:1 (wherein the molar amount of anhydrous ferrous sulfate is 2 mol) to 50 mL of deionized water in sequence. Heat and stir to completely dissolve the raw materials to obtain a uniform light green clear solution A.

[0064] Step 2: Use a spray drying method to spray the uniform solution A into precursor powder B, with the specific parameters being: 100% air inlet rate, 200°C air inlet temperature, and 15% feed rate (the actual feed rate accounts for the maximum feed rate of 100% acceptable to the equipment).

[0065] Step 3: Transfer the precursor powder B to a tube furnace for calcination. The calcination conditions are: in an argon atmosphere, first increase the temperature to 150°C at a heating rate of 3°C / min, keep the temperature for 4 hours, then increase the temperature to 400°C at a heating rate of 5°C / min, and keep the temperature for 20 hours. The calcined product is crushed, ground and sieved to obtain Na2Fe2(SO4)3 positive electrode material.

[0066] Comparative Example 3 (adding carbon nanotubes as a carbon source based on Comparative Example 2)

[0067] Preparation of carbon-coated Na2Fe2(SO4)3 cathode material:

[0068] Step 1: Add anhydrous ferrous sulfate, anhydrous sodium sulfate, and carbon nanotubes in a molar ratio of 2:10:0.03 (wherein the molar amount of anhydrous ferrous sulfate is 2 mol) into 50 mL of deionized water in sequence. Heat and stir to completely dissolve the raw materials to obtain a uniform light green clear solution A.

[0069] Step 2: Use a spray drying method to spray the uniform solution A into precursor powder B, with the specific parameters being: 100% air inlet rate, 200°C air inlet temperature, and 15% feed rate (the actual feed rate accounts for the maximum feed rate of 100% acceptable to the equipment).

[0070] Step 3: Transfer the precursor powder B to a tube furnace for calcination. The calcination conditions are: in an argon atmosphere, first increase the temperature to 150°C at a rate of 3°C / min, keep the temperature for 4 hours, then increase the temperature to 400°C at a rate of 5°C / min, and keep the temperature for 20 hours. The calcined product is crushed, ground and sieved to obtain Na+ with added carbon nanotubes. 2.1 Fe2(SO4)3 positive electrode material.

[0071] Comparative Example 4 (adding ascorbic acid as a carbon source based on Comparative Example 2)

[0072] Preparation of carbon-coated Na2Fe2(SO4)3 cathode material:

[0073] Step 1: Add anhydrous ferrous sulfate, anhydrous sodium sulfate, and ascorbic acid in a molar ratio of 2:10:0.03 (wherein the molar amount of anhydrous ferrous sulfate is 2 mol) into 50 mL of deionized water in sequence. Heat and stir to completely dissolve the raw materials to obtain a uniform light green clear solution A.

[0074] Step 2: Use a spray drying method to spray the uniform solution A into precursor powder B, with the specific parameters being: 100% air inlet rate, 200°C air inlet temperature, and 15% feed rate (the actual feed rate accounts for the maximum feed rate of 100% acceptable to the equipment).

[0075] Step 3: Transfer the precursor powder B to a tube furnace for calcination. The calcination conditions are: in an argon atmosphere, first increase the temperature to 150°C at a rate of 3°C / min, keep the temperature for 4 hours, then increase the temperature to 400°C at a rate of 5°C / min, and keep the temperature for 20 hours. The calcined product is crushed, ground and sieved to obtain Na 2.1 Fe2(SO4)3 positive electrode material.

[0076] Comparative Example 5 (the amount of carbon nanotubes added in Example 1 remains unchanged, and ascorbic acid is added in excess)

[0077] Carbon-coated fluorine-doped Na 2.01 Fe2(SO4)3F 0.01 Preparation of positive electrode materials:

[0078] Step 1: Anhydrous ferrous sulfate, anhydrous sodium sulfate, sodium fluoride, carbon nanotubes and ascorbic acid are added to 50 mL of deionized water in a molar ratio of 2:1:0.01:0.02:0.1 (wherein the molar amount of anhydrous ferrous sulfate is 2 mol). The raw materials are completely dissolved by heating and stirring to obtain a uniform light green clear solution A.

[0079] Step 2: Use a spray drying method to spray the uniform solution A into precursor powder B, with the specific parameters being: 100% air inlet rate, 200°C air inlet temperature, and 15% feed rate (the maximum feed rate acceptable to the equipment is 100% of the maximum pump speed).

[0080] Step 3: Transfer the precursor powder B to a tube furnace for calcination. The calcination conditions are: in an argon atmosphere, first increase the temperature to 150°C at a rate of 3°C / min, keep the temperature for 4 hours, then increase the temperature to 400°C at a rate of 5°C / min, and keep the temperature for 20 hours. The calcined product is crushed, ground and sieved to obtain carbon-coated fluorine-doped Na 2.01 Fe2(SO4)3F 0.01 Positive electrode material.

[0081] Performance Testing

[0082] The final products of Examples 1 to 5 and Comparative Examples 1-5 were mixed with a conductive agent (Super P) and a binder (polyvinylidene fluoride) in a mass ratio of 7:2:1, and then 150 μL of N-methylpyrrolidone (NMP) was added for dilution to form a uniform slurry. The slurry was evenly coated on the aluminum current collector and dried by blast drying at 60°C for 12 hours. The discs were cut into 1.2 cm in diameter using a cutting machine as the positive electrode of a sodium ion battery. A glass microfiber diaphragm was used, and the solvent of the electrolyte was diethyl carbonate and ethylene carbonate in a 1:1 volume ratio, and the solute was NaClO4. A sodium sheet of the same size as the positive electrode was used as the counter electrode and assembled into a half-cell. Electrochemical testing was performed after standing for 12 hours in a constant temperature environment of 25°C.

[0083] like Figure 1 The figure shows the battery rate performance of Example 2 and Comparative Example 1. The data in the figure clearly show that the carbon-coated fluorine-doped Na 2.05 Fe2(SO4)3F 0.05 The capacity of the positive electrode material at different rates is significantly better than that of comparative example 1 and the undoped F-carbon-coated Na2Fe2(SO4)3 positive electrode.

[0084] like Figure 2 The carbon-coated fluorine-doped Na 2.05 Fe2(SO4)3F 0.05 SEM image of positive electrode material. Figure 2 It can be seen that the spray-dried particles present an irregular round particle morphology, there is no obvious adhesion between the particles, and it is obvious that the tubular carbon material is embedded in the interior and surface of the particles.

[0085] like Figure 3 The figure shows the SEM image of the carbon-coated Na2Fe2(SO4)3 positive electrode material prepared in Comparative Example 1, which is similar to the SEM image of Example 2, and it can be seen that F doping does not affect the morphology change.

[0086] like Figure 4 The carbon-coated fluorine-doped Na 2.05 Fe2(SO4)3F 0.05 XRD diagram of positive electrode materials. The upper part of the horizontal line is carbon-coated fluorine-doped Na 2.05 Fe2(SO4)3F 0.05 The XRD of the sample corresponds one to one with the standard Na2Fe2(SO4)3 in the lower part, which confirms that trace doping will not change the overall structure of Na2Fe2(SO4)3.

[0087] like Figure 5 The carbon-coated fluorine-doped Na 2.05Fe2(SO4)3F 0.05 The first charge and discharge curve of the positive electrode material at 0.2C. The first cycle charge capacity at 0.2C is 102mAh·g -1 The first cycle discharge capacity is 96 mAh g -1 .

[0088] like Figure 6 The carbon-coated fluorine-doped Na 2.05 Fe2(SO4)3F 0.05 The 1C cycle performance diagram of the positive electrode material and the undoped carbon-coated Na2Fe2(SO4)3 positive electrode material of comparative example 1 as the positive electrode of a sodium ion battery shows that a small amount of fluoride ion doping can significantly improve the battery capacity and cycle stability.

[0089] Table 1

[0090]

[0091] As shown in Table 1, the following conclusions can be drawn: It can be clearly observed that the first discharge specific capacity of Example 1, Example 2 and Example 3 at different rates is significantly improved relative to Comparative Example 1, which indicates that trace amounts of fluoride ion doping can significantly improve the electrochemical performance of Na2Fe2(SO4)3 at different rates. The first discharge capacity of Example 1, Example 4 and Comparative Example 5 at different rates shows that an appropriate amount of carbon coating can significantly improve the electronic conductivity and discharge capacity of the electrode material, but the addition of excessive ascorbic acid will have a negative impact on the performance of the electrode material, especially reducing the ionic conductivity, the discharge capacity at a large rate and increasing the interface impedance. The addition amount of the two carbon sources in Example 1 is the addition amount corresponding to the best performance. The difference in the first discharge capacity storage at different rates between Example 1 and Example 5 is due to the fact that the reducibility of ascorbic acid is higher than that of citric acid, and ascorbic acid has good carbon formation due to its chemical structure, and is easily decomposed under heat treatment conditions to form a uniform carbon coating, and thus the conductivity and discharge capacity of the material will be higher, but Example 5 can still obtain better material performance than the comparative example. Compared with Example 2, Example 3 and Example 4 can effectively improve the discharge capacity of the battery by adding carbon nanotubes or ascorbic acid alone to achieve the encapsulation of Na2Fe2(SO4)3. However, compared with the carbon coating effect achieved by two carbon sources in Example 1, the capacity improvement is limited, indicating that the synergistic carbon coating of the two carbon sources in the present invention significantly enhances the electrochemical performance of Na2Fe2(SO4)3 at different rates. Finally, the comparison between Examples 1, 2 and 3 shows that if the amount of F element doping is too much, it will cause changes in the material structure and reduce its performance; while insufficient doping will not significantly improve the performance. Therefore, precise control of the doping amount of fluorine element is crucial to improving the rate performance of the material.

[0092] Table 2

[0093]

[0094] As shown in Table 2, the following conclusions can be drawn: By comparing Example 1 and Comparative Example 1, it can be seen that the doping of fluorine element effectively improves the stability of the battery cycle. Example 1 and Example 2 show that increasing the amount of fluorine element doping within a certain range can further improve the electrochemical cycle stability. By comparing Example 1 with Example 4 and Comparative Example 5, it can be seen that a suitable carbon source ratio can effectively improve the cycle stability of battery materials. Excessive carbon layer may cause unnecessary side reactions with the electrolyte during the cycle, affecting the stability of the CEI or SEI film, and thus affecting the cycle life of the battery. Example 1 and Example 5 show that ascorbic acid and citric acid are used as carbon source II, and the carbon layer formed is stable and of moderate thickness, which is conducive to conductivity and maintaining cycle stability. In addition, Example 2 and Example 3 show that if too much fluorine ion doping is added, the original main phase Na2Fe2(SO4)3 crystal structure will be seriously damaged, and the side reactions will increase with the generation of the impurity phase Na2S2O4, and the battery life will be reduced. From Comparative Examples 3 and 4 and Comparative Examples 1 and 2, it can be seen that the synergistic carbon layer coating of ascorbic acid and carbon nanotubes not only significantly improves the electronic conductivity of the electrode material, but also inhibits the side reactions between the electrode and the electrolyte, reduces the formation of by-products on the electrode surface, thereby maintaining the integrity of the electrode during the cycle, and further improving the cycle retention rate and long-term electrochemical performance of the material.

[0095] In summary, the carbon-coated fluorine-doped Na2Fe2(SO4)3 cathode material prepared by spray drying has good electrochemical performance. The invention has high production efficiency, low cost and is easy for commercial production, making it an effective method worthy of consideration in the preparation of sodium ion battery materials.

[0096] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0097] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a carbon-coated fluorine-doped sodium iron sulfate positive electrode material, characterized in that: The steps include: Step 1: adding an iron source, a sodium source, a sulfur source, a carbon source and a fluorine source into deionized water, and heating and stirring to completely dissolve the raw materials to obtain a solution A; the carbon source is a mixture of a carbon source I and a carbon source II, the carbon source I is a carbon nanotube, and the carbon source II is one or both of citric acid and ascorbic acid; Step 2: Convert solution A into precursor powder B using a spray drying method; Step 3: calcining the precursor powder B under inert atmosphere, crushing and grinding the obtained product to obtain a carbon-coated fluorine-doped Na2Fe2(SO4)3 positive electrode material.

2. The method for preparing the carbon-coated fluorine-doped sodium iron sulfate positive electrode material according to claim 1, characterized in that: In step 1, the iron source is any one or more of ferrous sulfate heptahydrate, ammonium ferrous sulfate, anhydrous ferrous sulfate and ferrous acetate.

3. The method for preparing the carbon-coated fluorine-doped sodium iron sulfate positive electrode material according to claim 1, characterized in that: In step 1, the sodium source is any one or more of sodium oxalate, sodium bicarbonate, anhydrous sodium acetate, sodium citrate, sodium sulfide, sodium salicylate and sodium hydroxide.

4. The method for preparing the carbon-coated fluorine-doped sodium iron sulfate positive electrode material according to claim 1, characterized in that: In step 1, the sulfur source is any one or more of anhydrous sodium sulfate, potassium sulfate and ammonium sulfate.

5. The method for preparing the carbon-coated fluorine-doped sodium iron sulfate positive electrode material according to any one of claims 1 to 4, characterized in that: In step 1, the fluorine source is any one or more of sodium fluoride, potassium fluoride and sodium trifluoroacetate.

6. The method for preparing the carbon-coated fluorine-doped sodium iron sulfate positive electrode material according to any one of claims 1 to 4, characterized in that: In step 1, the molar ratio of the iron source, sodium source, sulfur source, carbon source and fluorine source is (1.0-2.5): (1.0-2.5): (1.0-2.5): (0.1-1.0): (0.01-1).

7. The method for preparing the carbon-coated fluorine-doped sodium iron sulfate positive electrode material according to claim 1, characterized in that: In step 1, the heating and stirring method is to add the raw materials in deionized water in order according to the ratio, stir for 10 to 90 minutes, and then ultrasonically disperse for 10 to 90 minutes to obtain solution A.

8. The method for preparing the carbon-coated fluorine-doped sodium iron sulfate positive electrode material according to claim 1 or 7, characterized in that: In step 2, the inlet temperature of the spray drying is 100-230° C., the outlet temperature is 100-120° C., and the feed rate is 5-25%.

9. The method for preparing the carbon-coated fluorine-doped sodium iron sulfate positive electrode material according to claim 1 or 7, characterized in that: In step 3, the inert gas protection atmosphere for calcination is one of argon, argon-hydrogen mixed gas and nitrogen; the calcination conditions are: first increase the temperature to 100-200°C at a heating rate of 1-4°C / min, keep warm for 1-6h, then increase the temperature to 200-500°C at a heating rate of 1-5°C / min, and keep warm for 10-25h.

10. Use of the carbon-coated fluorine-doped sodium iron sulfate positive electrode material prepared by the preparation method according to any one of claims 1 to 9 in a sodium ion battery.

Citation Information

Patent Citations

  • Sodium ferrous sulfate / carbon nanotube composite positive electrode material, preparation method and sodium ion battery

    CN115172724A

  • Modified sodium ferric sulfate positive electrode material as well as preparation method and application thereof

    CN117476858A

Cited By

  • Modified sodium ferric sulfate positive electrode material as well as preparation method and application thereof

    CN121449109A

  • Method for regenerating waste ferric sodium sulfate positive electrode material by recycling high-value carbon source and PVDF (polyvinylidene fluoride)

    CN121507184A